BUILDING STUDENT CHARACTER: THE EFFORTS OF SCHOOL PRINCIPALS IN DEVELOPING THE QURANIC SCHOOL MOVEMENT PROGRAM - Savira, Himma; Rodliyah, St.; Gunawan, Gunawan (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to describe the forms of development of the Quranic school movement program at SMPN 3 Lumajang, to identify the principal's efforts in developing the program, and to analyze the impact of the program's development at SMPN 3 Lumajang. This research employs a qualitative approach with a case study type. The research subjects include the principal, teachers, students, and parents, with data collection techniques involving passive participatory observation, semi-structured interviews, and document analysis. Data analysis is conducted using inductive analysis, starting with data reduction, data presentation, and drawing conclusions. Validation is achieved through source triangulation, technique triangulation, and member checking. The results of this study indicate that the forms of development of the Quranic School Movement program at SMPN 3 Lumajang include the restructuring of the Quranic study system. Initially, students only read short surahs in a centralized manner, but now a tiered Quranic study system has been established according to students' abilities. This system has also been supplemented with Tilawati and Qur'ani methods. The school has added programs for tahfidz, extracurricular tilawah, and calligraphy. The principal's efforts in developing the Quranic School Movement program include building partnerships with Madin As-Sakinah, enhancing teachers' capabilities, and conducting regular coordination and evaluation. These efforts have had a positive impact on students, teachers, and parents/guardians.